Certain Aspects of Suspending Pre-Trial Investigations in Criminal Proceedings Under Martial Law - L. V. Tserkunyk (Bulletin of Kharkiv National University of Internal Affairs)
The article compares and highlights some of the grounds for suspending and resuming criminal proceedings under martial law. It has been established that, under the legal regime of martial law, the legislator has defined in certain sections of the Criminal Procedure Code of Ukraine the grounds for suspending pre-trial investigations and suspending the term of pre-trial investigations, and has also provided for the possibility of such decisions being taken by various authorised participants in criminal proceedings. The article highlights the practical aspect of applying the norms of criminal procedural legislation of Ukraine when deciding to suspend pre-trial investigations under martial law, in particular, citing as circumstances for such a decision the physical loss of access to criminal proceedings materials, material evidence, communication with the place of detention of the suspect, etc. At the same time, attention is focused on the practice of resolving the issue of extending the term of detention of a suspect until a decision is made to suspend criminal proceedings under martial law. Particular attention is paid to the consequences of the decision to resume pre-trial proceedings, as well as the cancellation of the decision to suspend the pre-trial investigation and to suspend the term of the pre-trial investigation. Emphasis is placed on the fact that the purpose of the institution of suspension of pre-trial investigation is to preserve the term of pre-trial investigation under the circumstances specified by criminal procedural law. It is concluded that the definition of the grounds for suspension of pre-trial investigation under martial law in separate sections of the Criminal Procedure Code of Ukraine is inappropriate and may lead to problems during practical implementation, create additional grounds for appealing such decisions, and the various consequences of cancelling decisions to suspend pre-trial investigations or suspend the term of pre-trial investigations may lead to abuse.